Studi Komparasi Pembelajaran Pendekatan Tarl Gaya Belajar ,CRT dan Integrasi falam Peningkatan Keterampilan Bola Basket - Oktavia, Hasna Tri; Setianingsih, Mega Rayhan Yuni; Assidiqi, Muadz; Raharjo, Hermawan Pamot (Gelanggang Olahraga: Jurnal Pendidikan Jasmani dan Olahraga (JPJO), 2025)
The purpose of this research is to analyze the most effective learning approaches in physical education. The subjects of this study are 11th-grade students at SMK Negeri H. Moenadi Ungaran (SPMA) with a total of 4 experimental classes and 1 instrument testing class. The design of this research uses mixed methods with the type of mixed methods being concurrent embedded design with a tendency towards quantitative-qualitative research. Data will be analyzed using IBM SPSS Version 25. The results of this study indicate that all treatments had a significant impact on student learning outcomes. However, the highest sequential improvement comes from the Integration, Learning Style, TaRL, and CRT groups. Conclusion: Learning with the integration of CRT, TaRL, and learning styles has a positive impact compared to separate approaches. Keywords: Learning Approaches, TaRL, CRT, Learning Styles, PJOK